Structure of semiconducting versus fast-ion conducting glasses in the Ag–Ge–Se system - Anita Zeidler; Philip S. Salmon; Dean A. J. Whittaker; Andrea Piarristeguy; Annie Pradel; Henry E. Fischer; Chris J. Benmore; Ozgur Gulbiten (Royal Society Open Science, 2018)
The transition from a semiconductor to a fast-ion conductor with increasing silver content along the Agx(Ge0.25Se0.75)(100−x) tie line (0≤x≤25) was investigated on multiple length scales by employing a combination of electric force microscopy, X-ray diffraction, and neutron diffraction. The microscopy results show separation into silver-rich and silver-poor phases, where the Ag-rich phase percolates at the onset of fast-ion conductivity. The method of neutron diffraction with Ag isotope substitution was applied to the x=5 and x=25 compositions, and the results indicate an evolution in structure of the Ag-rich phase with change of composition. The Ag–Se nearest-neighbours are distributed about a distance of 2.64(1) Å, and the Ag–Se coordination number increases from 2.6(3) at x=5 to 3.3(2) at x=25. For x=25, the measured Ag–Ag partial pair-distribution function gives 1.9(2) Ag–Ag nearest-neighbours at a distance of 3.02(2) Å. The results show breakage of Se–Se homopolar bonds as silver is added to the Ge0.25Se0.75 base glass, and the limit of glass-formation at x≃28 coincides with an elimination of these bonds. A model is proposed for tracking the breakage of Se–Se homopolar bonds as silver is added to the base glass.